Educar o jovem para ser útil à si e à sua Pátria: a assistência pela profissionalização, Rio de Janeiro (1894 1932) - Maria Zelia Maia de Souza (2013)
This thesis has the Instituto Profissional João Alfredo (IPJA) as objective in the period comprehended between the years of 1894 and 1932. Located in the Federal District this institution of social assistance and school was created to shelter, educate and instruct destitute young men, in the age group of 12 and 15 years old. The objective of this study is to demonstrate that the IPJA was established as a part of the assistance public politics of the time characterized by the articulation between social assistance and professional education. To understand the tensions between the social assistance and the professional education, the municipal laws related to the theme and the debates produced by educators, jurist and doctors were analyzed. It was also investigated the relations between the urban reforms that took place in the Federal District and the educational reforms. For the historical analysis of the IPJA, it was used as reference bibliographic studies performed in the field of history of education, as well as theoretic analysis in the domain of social education history. As for the documental research, I investigated documents sent to the Public Primary Instruction Administration, mayors' messages, city hall's reports, specific legislation to the theme and students' files/dossier of the institution. This study made possible to observe that the professional activities of the IPJA were altered throughout the analyzed period. It's noticeable that, initially, there is the predominance of the artisanal crafts' teaching and, at a later time, of those crafts related to the industrial work. In this way, the action plan of the Federal District's municipality stimulated the increase of the professional teaching program of IPJA, providing the establishment of the specialized knowledge of electromechanics. As for the students, if by one side, during the years of 1920, there was a substantial increase in the number of enrolments in the IPJA showing a demand for the professional teaching, on the other hand, it was observed that most of the students didn't finish the professional course. These were signs that the Federal District's municipality faced limits to make feasible the assistance through the professionalization in the IPJA.